Intercultural relations and religious authorities Muslims in the European Union - Shadid, W. A. R.; Koningsveld, P. Sj. van (Peeters, 2002)
The permanent presence of Islam and Muslims in the countries of the European Union implies many different forms of intercultural relations at different levels of society, as for instance, between Muslims and other religious or philosophical groups, within the framework of social and health care, in city life and within the sector of education. They have been grouped into four main categories: their position in the countries of the European Union, especially in the press, in schoolbooks and in local politics; between Muslims and other groups and institutions in the countries concerned, as stereotypes and prejudices can exercise a detrimental effect upon intercultural relations within many different sectors of society; religion and education, and especially the Islamic Religious Education as well as the religiousness of Muslim and non-Muslim pupils; authorities of the Muslim communities in the countries of the European Union and their contribution to the formation of a "European Islam". In this context special attention is paid to the role Muslim religious authorities play in the discussions concerning political participation by Muslims in the West.